Design and testing of systolic array multiplier using fault injecting schemes - Kurada Verra Bhoga Vasantha Rayudu; Dhananjay Ramachandra Jahagirdar; Patri Srihari Rao (Institute of Advanced Engineering and Science, 2022)
Nowadays low power design circuits are major important for data transmission and processing the information among various system designs. One of the major multipliers used for synchronizing the data transmission is the systolic array multiplier, low power designs are mostly used for increasing the performance and reducing the hardware complexity. Among all the mathematical operations, multiplier plays a major role where it processes more information and with the high complexity of circuit in the existing irreversible design. We develop a systolic array multiplier using reversible gates for low power appliances, faults and coverage of the reversible logic are calculated in this paper. To improvise more, we introduced a reversible logic gate and tested the reversible systolic array multiplier using the fault injection method of built-in self-test block observer (BILBO) in which all corner cases are covered which shows 97% coverage compared with existing designs. Finally, Xilinx ISE 14.7 was used for synthesis and simulation results and compared parameters with existing designs which prove more efficiency.